Impedance spectroscopy and electrical conductivity of 0.7BiNdxFeO3–0.3BaTiO3 ferroelectric ceramics - Hui Tang; Xiao-Cao Peng; Jiu-Ming Ma; Zhi-Peng Yang; Xiang Niu; Jun-Xia Wen; Xin-Gui Tang; Sheng-Guo Lu (Journal of Advanced Dielectrics)
0.7Bi[Formula: see text]NdxFeO3–0.3BaTiO3 (BNFO–BTO, [Formula: see text], 0.010, 0.020 and 0.050) ceramics were fabricated using the high-temperature solid-state reaction method. The X-ray diffraction (XRD) patterns revealed that the primary phase in these ceramics was pseudocubic. The Scanning Electron Microscopy (SEM) micrographs exhibited dense microstructures throughout all BNFO–BTO ceramics. Furthermore, the temperature dependence of dielectric behaviors and ferroelectric hysteresis loop shapes suggested the occurrence of a relaxor ferroelectric-type phase transition in BNFO–BTO ceramics. Additionally, the frequency dispersion characteristics and remnant polarization were enhanced with increasing substitution of Bi[Formula: see text] by Nd[Formula: see text]. Conducted impedance analysis on 0.7Bi[Formula: see text]NdxFeO3–0.3BaTiO3 ceramics and two dielectric responses of the grain at high frequency and grain boundary at low frequency were illustrated, respectively. The combination of imaginary impedance ([Formula: see text] and imaginary modulus ([Formula: see text] versus log[Formula: see text]f plots revealed that the charge carriers’ motion was not entirely long-range, short-range migration also exists. Through calculations based on Curie–Weiss Law, the relaxation activation energy ([Formula: see text] and conductance activation energy ([Formula: see text] were investigated, confirming that doping Nd[Formula: see text] effectively mitigates the concentration of oxygen vacancies (OVs) and prevents the formation of oxygen vacancies clusters, ultimately suppressing conductivity in BNFO–BTO ceramics.